ANALISIS DAMPAK LINGKUNGAN PERKEMBANGAN INDUSTRI TERHADAP KESEHATAN MASYARAKAT DI KABUPATEN BOYOLALI - Heru Nur Alamsyah; Yosep Natan Nitit; Muryanto; Akhyari; Silitonga, Frangky; Sermatutar Luhur Imam Seto; Sermadatar Dimas Widhi Nugraha (JURNAL MAHATVAVIRYA, 2024)
Public health as the science and art of preventing disease, prolonging life, and improving the quality of life by making organizational efforts and providing informed choices to communities, organizations, communications, and individuals. The goal of national development is the full human development of Indonesia. Namely Indonesian human development both physically and mentally, human development is basically an effort to humanize humans again. Keyongan village, Nogosari Sub-District, Boyolali regency as an area for medium-sized industries in the form of Agriculture, paper, wood industry, publishing, printing, apparel and similar industries. This is in accordance with Rpjm Kab. Boyolali since 2010 now 2024 which launched the program “Pro Invenstment". In this study raised public health issues with the environment of Agriculture and medium industry in Keyongan Village, Nogosari District, Boyolali regency, and using qualitative research methods. The objective was to find out the health condition of the people of Keyongan village, with the emergence of various medium-sized industries in the vicinity and to find out the efforts made by the community and the village government to maintain public health. The growth of various entrepreneurial activities, especially being a medium-sized industrial area, will leave a residue for the environment, both in terms of sound or noise, air or pollution, unpleasant odors, the development of flies and mosquitoes due to water pollution from industrial waste and so on. This term if not managed properly will cause prolonged adverse effects, especially for the health of both individuals, groups and communities.